Comparative volatile profiling of mango (Mangifera indica) and its role in mediating chemoecological behaviour of mango pulp weevil (Sternochetus frigidus) - Begum, Sayesta Mehejaveen; Bhattacharyya, Badal; Borkataki, Shimantini; Hazarika, Bikash; Gogoi, Dhanalakhi; Bhairavi, K Sindhura; Gogoi, Inee (Frontiers in Insect Science, 2026)
IntroductionThe volatiles from Mango tree play a critical role in mediating interactions with herbivores, including the mango pulp weevil (Sternochetus frigidus), a serious quarantine pest of mango. The monophagous feeding habit and concealed life cycle of mango pulp weevil within fruits render insecticides, quarantine measures and post-harvest treatments largely ineffective. Identifying volatile cues emitted by the mango tree that mediate host location can aid in developing eco-friendly management strategies.MethodsIn this study, Volatile Organic Compounds (VOCs) from different mango tree parts viz., young flush, mature flush, stem, flower, stone, whole and sliced green fruits, whole and sliced ripened fruits were characterized through solvent extraction and Gas Chromatography-Mass Spectrometry (GC-MS). The behavioural responses of adults were evaluated through Y-tube olfactometer assays.Results and discussionRipened mango fruits, young leaves and mango stone elicited the strongest responses and were further subjected to headspace volatile collection. Ripened fruit volatiles induced the highest levels of attraction (63.33%), activity (86.67%) and preference (46.15%). Young leaf volatiles induced moderate attraction (46.7%) with high activity (83.3% but low preference (12%). Mango stone volatiles, in contrast, evoked minimal activity (6.7%) and preference (10%). GC-MS profiling of headspace extracts revealed nine compounds each from ripened fruits and young leaves and seven from stones, with D-limonene, 3-carene and α-pinene dominating across all treatments. These findings highlight key VOCs associated with host selection by Sternochetus frigidus and provide a chemical basis for developing attractant-based trapping systems as components within a holistic Integrated Pest Management (IPM) approach in mango cultivation.